1999
DOI: 10.1042/cs19980340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adrenaline on glucose and glutamine metabolism and superoxide production by rat neutrophils

Abstract: Despite the large body of information on the role of corticosteroids in regulating lymphocyte and phagocyte function, the role of the hormone adrenaline in immunoregulation is an under-investigated topic. The present study has addressed the effects of adrenaline on the rates of utilization and oxidation of glucose and glutamine, the phagocytic capacity and the rate of superoxide production by rat neutrophils. Incubation of rat neutrophils in the presence of 50 microM adrenaline caused a marked elevation in glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…In a previous study, we found that glutamine may give rise to substantial quantities of NADPH for superoxide production in rat neutrophils. 10 Similar observations have been obtained in neutrophils from postoperative patients. 11 This fact explains the observations that glutamine enhances the bactericidal function of neutrophils from normal patients and those suffering from burns.…”
Section: Introductionsupporting
confidence: 79%
“…In a previous study, we found that glutamine may give rise to substantial quantities of NADPH for superoxide production in rat neutrophils. 10 Similar observations have been obtained in neutrophils from postoperative patients. 11 This fact explains the observations that glutamine enhances the bactericidal function of neutrophils from normal patients and those suffering from burns.…”
Section: Introductionsupporting
confidence: 79%
“…Cyclic AMP is known to be the second messenger of ß-adrenergic receptors (23). Thus, due to the fact that the most pronounced changes in glycogen breakdown were observed for isoproterenol, in the second set of experiments the effect of dibutyryl cyclic AMP was tested.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of glucose-6phosphate dehydrogenase (G6PDH; EC 1.1.1.49) was determined as previously described. 4,10 The extraction medium contained 50 mM Tris-HCl and 1 mM EDTA; the final pH was 8.0. For the enzyme assay, Triton X-100 0.05% (v/v) was added to the assay system to complete the extraction of the enzyme.…”
Section: Glutaminase (Phosphate-dependent) and Glucose-6phosphate Dehmentioning
confidence: 99%
“…Evidence has been obtained that glucose metabolism is required both for new membrane synthesis during active periods of phagocytosis and for production of NADPH (through the pentose phosphate pathway). 5,6 The metabolism of glutamine has been associated with phagocytosis 7,8 and production of O :À 2 , [9][10][11] and TNF 12 by neutrophils.…”
Section: Introductionmentioning
confidence: 99%